Input-Output Analysis: a Case Study of Transportation Sector in Indonesia - Muryani; Swastika, Rosario Bedi (Journal of Developing Economies, 2018)
This study Aimed to analyze the transport linkages and multiplier effects of each subsector of transport when there is a change in the budget of the transport sector in the Indonesian economy. This study uses an analytical tool input - output models of Indonesia in 2010, with 185 sectors. Input - output models is used to analyze the relationship backwards and forwards in the transport sector of the Indonesian economy and the multiplier effect on the Indonesian economy as a whole. Results of the analysis Showed that the transport has a total backward linkage high while total forward linkage of transport is relatively low. This is an indication that transportation plays in attracting and developing the upstream sector, but less instrumental in developing the downstream sector. The results Obtained from the analysis of the output multiplier effect when a decline in the transport sector budget has a high value, while the income multiplier and labor multiplier when a decline in the transport sector budget has a low value. This shows a Decrease in the budget in the transport sector can reduce the production output of the Indonesian economy but less budget reduction effect on income and employment. Keywords: Transportation, input-output, linkage forward, backward linkages, multiplier effects JEL Classification: L98, R15